2017
DOI: 10.21276/apalm.1428
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of prostate specific antigen in comparison with histological grade of prostatic adenocarcinoma: A Hospital based study.

Abstract: Background: Prostate gland disease causes significant morbidity in elderly males. Our objective of the study was to evaluate the histopathological spectrum of prostatic lesions in correlation with prostate specific antigen and compare the prostate specific antigen with histological grade of prostatic adenocarcinoma. Methods:The present retrospective study was carried in the department of pathology, Narayana Medical College & Hospital, Nellore, and Andhra Pradesh, India from January 2015 to December 2015. 119 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Nadam et al 21 found 5.88% malignant cases having PSA level 0-≤4 ng/ml, 82.3% malignant cases having PSA level >10 ng/ml and 11.76% malignant cases having PSA level 4.1-10 ng/ml. similarly Nadam et al 21 found 51.58% benign cases having PSA level 0-≤4 ng/ml, 5.26% benign cases having PSA level >10 ng/ml and 43.16% benign cases having PSA level 4.1-10 ng/ml. Sladana Zivkovic et al 22 found 2.50% malignant cases having PSA level 0-≤4 ng/ml, 70% malignant cases having PSA level >10 ng/ml and 27.50% malignant cases having PSA level 4.1-10 ng/ml.…”
Section: Discussionmentioning
confidence: 89%
“…Nadam et al 21 found 5.88% malignant cases having PSA level 0-≤4 ng/ml, 82.3% malignant cases having PSA level >10 ng/ml and 11.76% malignant cases having PSA level 4.1-10 ng/ml. similarly Nadam et al 21 found 51.58% benign cases having PSA level 0-≤4 ng/ml, 5.26% benign cases having PSA level >10 ng/ml and 43.16% benign cases having PSA level 4.1-10 ng/ml. Sladana Zivkovic et al 22 found 2.50% malignant cases having PSA level 0-≤4 ng/ml, 70% malignant cases having PSA level >10 ng/ml and 27.50% malignant cases having PSA level 4.1-10 ng/ml.…”
Section: Discussionmentioning
confidence: 89%